2015
DOI: 10.1108/cr-09-2013-0073
|View full text |Cite
|
Sign up to set email alerts
|

The role of joint actions in the performance of IT clusters in Mexico

Abstract: Purpose -The purpose of this article is to show the importance of joint actions and institutions for collaboration (IFCs) in the development and performance of information technology (IT) business clusters in the context of Mexico. Design/methodology/approach -A review of the literature suggests the types of linkages that the clusters must develop to be successful in the context of emerging countries. Two IT clusters in the region of Puebla and Jalisco are compared to highlight the factors that differentiate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Extant research has focused on cluster initiatives that use the country (Wilson et al, 2014) or the subnational region (Gutiérrez-Martínez et al, 2015) as geographic units of analysis. This paper focuses on the supra-national region and conducts a historical account of the Central American Competitiveness Initiative.…”
Section: Introductionmentioning
confidence: 99%
“…Extant research has focused on cluster initiatives that use the country (Wilson et al, 2014) or the subnational region (Gutiérrez-Martínez et al, 2015) as geographic units of analysis. This paper focuses on the supra-national region and conducts a historical account of the Central American Competitiveness Initiative.…”
Section: Introductionmentioning
confidence: 99%
“…The perception of high risk may even constitute an obstacle to meaningful collaboration between competitors (Arranz and Arroyabe, 2008). In a similar vein, some authors have suggested that coopetition may not represent an appropriate strategy to the production of new innovations (Nieto and Santamaria, 2007; Ritala and Hurmelinna-Laukkanen, 2009; Gutierrez-Martínez et al , 2015). Different innovation related objectives lead to different levels of value/tensions over the appropriation among co-competitors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…R&D cooperation relationships have been identified as an important factor in explaining differences in innovation levels, not only between firms but also between regions (Fritsch, 2004). The main focus of the last two decades of coopetition research has primarily investigated these aspects of change, and cooperation among competitors has been studied within many research areas, with or without labeling the relationship as “coopetition” (Bengtsson and Kock, 2014), in many sectors, including ICT (Gueguen, 2009; Gutierrez-Martínez et al , 2015), healthcare (Barretta, 2008; Peng and Bourne, 2009), air transport (Garrette Castañer and Dussauge, 2009), food (Kotzab and Teller, 2003) automotive industry (Gwynne, 2009; Segrestin, 2005); services (Mention, 2011), semiconductor industry (Park et al , 2014), tourism (Della Corte and Aria, 2016), medical and machinery sectors (Bouncken et al , 2017), even while no study has yet simultaneously involved different industries.…”
Section: Introductionmentioning
confidence: 99%
“…They find that BGFs with both technological leadership and entrepreneurship orientation can follow an integrated strategy whereas firms with technological leadership would adopt the differentiation strategy and firms with entrepreneurial orientation adopt a cost leadership strategy. In addition, studies have also emphasized the importance of location (clusters such as Bangalore) on innovativeness, competitiveness and performance of BGFs (Gutiérrez-Martínez et al , 2015; Manzini and Di Serio, 2017; Momaya, 2016). While studies examining internationalization paths of BGFs do examine the individual dimensions such as international scope, nature of commitment, strategic orientation, none of these studies examine these dimensions in an integrated manner.…”
Section: Review Of Literaturementioning
confidence: 99%